Determining the characteristics of the green consumer and their marketing implications - Goh, Seng Vei (2015)
It is the belief that the current trend towards environmental consciousness is a relatively unexplored area with vast potential to develop into a successful and lucrative market that motivated our team to carry out this study. The focus of the research is on the determination of the characteristics of the environmentally conscious consumer and how he or she is different from the non-environmentally conscious consumer in terms of attitudes, personality, demographic and social characteristics. Moreover, attitudes towards the marketing of green products by both groups of consumers are also investigated. Results of the study indicate that environmentally conscious consumers tend to belong to the pre-middle age group, have secondary school educational qualifications and above and possess middle to high occupational status. On the other hand, non-environmentally conscious consumers are found to be less concerned with environmental risks, less tolerant, more status-conscious and less cosmopolitan in outlook. Furthermore, they tend to have lower perceived consumer effectiveness too. However, both groups were found to be equally status conscious. The study shows that the marketing of green products in Singapore can be much improved in terms of distribution. It also shows that environmentally conscious consumers are more willing to pay higher prices for green products than non-environmentally conscious consumers. The former are also less concerned with fanciful packaging of green products and are more aware of the promotion of green products. However, both groups of consumers perceive that green and non-green products would perform equally well and they also see no differences between branded and non-branded green products. The research carried out thus provided useful information and implications for developing effective marketing tactics. By knowing the differences between environmentally and non-environmentally conscious consumers, marketers can better understand the needs of both groups. Hopefully, this would enable marketers to come up with products that can satisfy their needs.